Electromagnetic theory of nanodimensional antennas for terahertz, infrared and optical regimes - Slepyan, G.Ya; Shuba, M.V.; Nemilentsau, A.M.; Maksimenko, S.A. (2008 12th International Conference on Mathematical Methods in Electromagnetic Theory, 2008)
An electrodynamical theory of the vibrator nanoantenna based on the different types of carbon nanotubes (CNTs) has been presented. The theory covers a wide frequency range from terahertz to optical frequencies. It is based on the quantum-mechanical description of the CNT conductivity. The boundary-value electrodynamical problem has been formulated using the effective boundary conditions method and has been solved by the integral equations technique. As a result, a number of general properties of CNT-based nanoantennas have been revealed. These properties are very promising for potential applications in nanoelectronics, high resolution near field optical microscopy, thermal microscopy, etc.